PERHITUNGAN PREMI TAHUNAN TIDAK KONSTAN DAN CADANGAN BENEFIT ASURANSI LAST SURVIVOR DWIGUNA - SAEFULOH, SANI; WIDANA, I NYOMAN; HARINI, LUH PUTU IDA (E-Jurnal Matematika; Vol 9 No 2 (2020)DO - 10.24843/MTK.2020.v09.i02.p286, 2020)
Last Survivor Insurance is life insurance for two or more participants with premiums paid until the death of the last participant. This study discusses last survivor endowment insurance for two participants in a married couple. Compensation is paid after the second person dies or both stills alive after the end of a contract. The purpose of this study is to determine the value of non-constant annual premium and benefits reserves in the last survivor endowment insurance. The equivalence principle is used for calculation of premiums. Furthermore, the benefit reserve formula is determined using a prospective method. The value of the benefit reserve will continue to increase as long as premium payments are still being made.